Superficial Temporal Artery and Vein as Recipient Vessels for Scalp and Facial Reconstruction: Radiographic Support for Underused Vessels - Doscher, Matthew; Charafeddine, Ali H.; Schiff, Bradley A.; Miller, Todd; Smith, Richard V.; Tepper, Oren; Garfein, Evan S. (Journal of Reconstructive Microsurgery, 2015)
Background The choice of the recipient vessels for microsurgical reconstruction is based on proximity to the defect, vessel caliber, anatomic reliability, and ease of dissection. Traditionally in head and neck reconstruction, the superficial temporal artery and vein (STA/V) have been reserved as secondary recipient vessels. Others, including the facial artery (FA) and vein have been the preferred choice for facial reconstruction.Methods A retrospective analysis of all consecutive head and neck reconstructions using the STA/V by the senior author (E.S.G.) over a 5-year period was performed. Perioperative data were reviewed for all the patients. In a subset of patients, radiographic analysis was used to delineate STA and FA anatomy including vessel diameter and distances to standard anatomic landmarks.Results A total of 31 patients had 32 microsurgical reconstructions using the STA/V as recipient vessels. Radiographic analysis revealed no significant difference between the STA and FA diameters. The distances from the STA to the upper and middle face were significantly shorter relative to the FA, 64 versus 102 mm (p < 0.0001) and 72 versus 80 mm (p < 0.04), respectively. The distances from the lower face to the STA and FA were 56 and 30 mm, respectively (p < 0.0001).Conclusions The STA/V can be used as first choice recipient vessels in head and neck reconstruction. Key features of these vessels include proximity to defect, acceptable caliber, predictable anatomic location, and relative ease of dissection. We recommend that the STA/V be considered recipient vessels of choice for reconstruction of defects of the face and scalp.
Keywords: head and neck reconstruction; superficial temporal artery; recipient vessels